PERANCANGAN KOMUNIKASI VISUAL GUNA MEMBERI EDUKASI BAGI REMAJA PECANDU MOBILE ONLINE GAMES - HERNANDA, LAMBANG (DeKaVe, 2020)
The rapid development of science and technology brings changes in all walks of life. Human creativity is growing so as to encourage the acquisition of new findings in the field of technology that is used as a means of improving the welfare of humanity. One product of human creativity is an online game. As a media, internet games are very influential on the human mind which is absorbed through the two senses, namely seeing and hearing.Online gaming is a new lifestyle for some people in every age group. In the perspective of sociology, people who make online games opium, tend to be egocentric and put forward individualism. This is dangerous for the social life of the individual, they naturally move away from the surrounding environment and it is possible to marginalize themselves so that they assume that their life is in cyberspace and their social environment is only where they play the game. From the problems above, we need a solution that is expected to reduce, manage the level of addiction to mobile online games for adolescent behavior. This design is expected to be able to contribute to the prevention and management of mobile online games addiction for teenagers so that the future of the nation's next generation is more qualified.